ICT Law Book - Mambi, Adam J. (Dar es Salaam Mkuki na Nyota, 2010)
Recent developments in Information and Communication Technologies (ICT) have brought about changes that have revolutionalised traditional ways of conducting business. While these developments in cyberspace bear legal implications, legal regimes in some African countries such as Tanzania have not kept pace with the changes in order to properly regulate related activities happening under cyberspace. This volume attempts to bridge the gap between the Law and ICT developments in East Africa. It attempts to respond to questions such as: What is Cyber Law? How are Parties Identified under a Relationship in a Cyberspace Environment? How are Banking and other Cyber Payments Done? What about Combating Cyber Crime and Managing E-Commerce? What is the Impact of ICT on Intellectual Property Rights? And, how are Internet Domain Names Regulated? The volume is a useful handbook for those who want to understand the changing legal guidelines in relation to developments in ICT.
includes bibliographies and index
Keywords: ICT Law Book